(untitled) (Research, Society and Development, 2021)
Introduction: Although studies indicate that only 15% of Brazilian women at the beginning of pregnancy show interest in cesarean section, the number of surgical births exceeds the 10% to 15% recommended by WHO. It is important that the health professional provides an exchange of information and sharing of decisions between caregiver and care, instead of imposing knowledge. Objectives: To identify the health education actions provided to women during prenatal care regarding the parturition process; To know women’s perceptions about health education actions in relation to labor and delivery disclosed in prenatal care. Methodology: The study will be a field research, descriptive and exploratory, with a qualitative approach. The research participants will be puerperal women who are interned in the joint accommodation of a municipal maternity in the west zone of Rio de Janeiro, who accept to participate in the research, aged between 18 and 45 years old who have had a minimum of 6 (six) pre consultations -Christmas. After submission and approval by the Research Ethics Committee of UERJ and the city hall, data collection will begin, where semi-structured interviews will be conducted. Results: Based on the study, two categories were elaborated to discuss the theme. Category 1: Health education actions provided to women during prenatal care about the parturition process. Category 2: To know the perceptions of women about health education actions in relation to labor and childbirth disseminated in prenatal care. Final Considerations: During the research it was possible to observe the precariousness of information on the part of pregnant women and parturients, for this reason, it is understood that the preparation for the moment of delivery is essential during the meetings in the prenatal consultations, so that these women become stronger and conduct pregnancy and childbirth more autonomously.